LIS Education in India and Employability of Students: Issues and Challenges - Koteswara Rao, M. (Journal of Information and Knowledge, 2022)
The paper examines the growth and development of Library and Information Science (LIS) education in India in terms of the number of LIS schools and the proliferation of LIS courses across the country. It examines the problems, lacunae and quality control issues in the present LIS education system, which has led to rising unemployment or under-employment. The paper discusses the ‘employability’ of LIS students against a highly competitive job market impacted by the developments in information and communication technologies. A few corrective measures have been suggested to improve the quality and standard of LIS education in the present digital information world.